2009
DOI: 10.2116/analsci.25.161
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of Analytical Sensitivity by Ar-N2 Inductively Coupled Plasma in Axially Viewing Optical Emission Spectrometry

Abstract: An inductively coupled plasma (ICP) is widely used for trace element analysis as an appropriate excitation source and an ionization one for optical emission spectrometry (ICP-OES) 1 and mass spectrometry (ICP-MS), 2,3 respectively. Although innovative efforts have been conducted to achieve further improvements in analytical sensitivity for both ICP-OES and ICP-MS, no reports have been found for axially viewing ICP-OES. In the 1980's, many examinations were performed on ICP-OES to improve the analytical sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…Since the central channel of Ar-N2 ICP became slightly narrower with an increase of the N2 gas flow rate, larger enhancements of the elements were observed for higher N2 gas flow rates, especially for up to 0.5 L min -1 observed in our previous study. 32 Although strong correlation between the excitation temperatures and the N2 gas flow rates could not be seen in the present study, improvements of the analytical sensitivity of the elements on the Ar-N2 ICP reported in our previous study 32 could be elucidated qualitatively.…”
Section: Emission Intensities and Excitation Behavior Of Elementscontrasting
confidence: 48%
See 3 more Smart Citations
“…Since the central channel of Ar-N2 ICP became slightly narrower with an increase of the N2 gas flow rate, larger enhancements of the elements were observed for higher N2 gas flow rates, especially for up to 0.5 L min -1 observed in our previous study. 32 Although strong correlation between the excitation temperatures and the N2 gas flow rates could not be seen in the present study, improvements of the analytical sensitivity of the elements on the Ar-N2 ICP reported in our previous study 32 could be elucidated qualitatively.…”
Section: Emission Intensities and Excitation Behavior Of Elementscontrasting
confidence: 48%
“…This trend was similar to that of the Mg II/Mg I intensity ratio, which was related to the electron number density of the analytical zone in the Ar-N2 ICP, observed in our previous study. 32 The increase in the excitation temperature was considered to be attributed to the plasma shrunken by the thermal pinch effect 4,5,[29][30][31] which resulted in the enhancement of the interaction between the plasma and the sample. Since, the excitation temperature increased, the Ar-N2 ICPs could be expected to possess a higher analytical capability than that of the standard ICP for axially viewing ICPOES.…”
Section: Excitation Temperature Of Ar-n2 Icpmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10][11][12][13][14][15][16] In addition, Ar-N 2 -ICP proved usefulness in reducing oxides and Ar polyatomic ions, which are interferents in ICP-MS. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Researches dealing with the use Ar-N 2 -ICP in axially viewed plasma in ICP OES have been quite limited. Ohata et al 36 demonstrated that plasma robustness (i.e., Mg(II)/Mg(I) ratio) were improved by using 1.3% of N 2 in the outer gas, 2 | J. Name., 2012, 00, [1][2][3] This journal is © The Royal Society of Chemistry 2012…”
Section: Introductionmentioning
confidence: 99%